Hukum Menghidupkan Tanah Mati ( Ihya ul mawat) dalam Perspektif Kitab Fathul Qarib - Arumsari, Ai Putri (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
Ihya' ul-Mawat is a concept in Islamic law that pertains to the effort of reviving or utilizing dead land that has not yet been owned. This practice has legal consequences for land ownership if it is carried out in accordance with Sharia principles. The aim of this article is to examine the legal provisions, requirements, and implications of land ownership based on the explanation of Shafi'i fiqh in the book Fathul Qarib, as well as its relevance to land utilization. The method used in this study is a historical research method with a library research approach, including content analysis of the Fathul Qarib text and supporting fiqh literature. The findings of the study indicate that reviving dead land is permissible and can be a means of acquiring ownership if it satisfies two conditions: first, the individual performing the action must be a Muslim and must have government permission, and second, the land must be unclaimed, meaning it is not previously owned by someone else. This study contributes to a better understanding of the legal framework surrounding the use and ownership of dead land in Islamic law.